Prevalence of solar UV-provoked anterior segment eye diseases and association of risk factors among fishermen in Jazan, Saudi Arabia - Alibrahim, Ahmed I. A. (2017)
Excessive exposure to ultraviolet (UV) radiation poses a serious threat to human health and safety especially among the outdoor workers. It can cause various types of eye disease such as cataract, pterygium, photoconjunctivitis, photokeratitis and pinguecula. Thus, this study was conducted with the aim to investigate the prevalence of solar UV provoked anterior eye segment diseases and the associated risk factors among on fishermen of Jazan. This cross -sectional study was conducted among fishermen in five ports of coastal areas in Jazan in Saudi Arabia. A questionnaire was used to determine the socio demography and occupational information of the fishermen. An eye examination was conducted for all of the respondents. The results obtained from this study discovere d a significant association between working experiences with some of the UV -related anterior segment eye diseases (p > 0.05). Moreover, this study found that days of work per week gave a significant influence to the eyelid in the right and left eye as well as overall eyelid diseases (p < 0.05). Besides, number of working hours per day was also recorded to have a significant association with conjunctival lesion/mass in the left eye and overall conjunctival mass since the p values are less than 0.05. Similarly, the place of resting, time of work, the use of hat outdoors, knowledge on UV, use of sunglasses and types of uniform during fishing have also demonstrated an association with a number of UV -related anterior segment eye disorders as their p values are less than 0.05. However, based on the multiple logistic regression analysis, the results is corresponding with previous studies where the risk of overall eye diseases significantly increases by 1.76 times for those who have worked for more than 10 years as f isherman compared to those who have worked less than 10 years.